Genetic Counselling Empowers Parents of Children with Intellectual Disabilities : A Fragile X Syndrome Perspective - Amir, Mentari; Aulia, Siti Farhanah; Ranakusuma, Octaviani Indrasari; Faradz, Sultana MH (Faculty of Medicine, Universitas Diponegoro, 2025)
Background: Intellectual disabilities (ID) profoundly affect individuals and their families, leading to financial strain, emotional distress, and limited access to healthcare and education. Fragile X Syndrome (FXS), the most common inherited cause of ID, remains largely underdiagnosed in Indonesia due to limited awareness and resources. Objective: This study aimed to assess the impact of genetic counselling on parental empowerment. Methods: This pre-experimental study employed a before and after counselling. A total of 238 parents of children with ID from four special schools in Jakarta participated. Data were collected using the Genetic Counselling Outcome Scale-24 (GCOS-24), which assesses empowerment. Purposive sampling was applied, and data were analysed using paired t-tests and one-way ANOVA. Results: The mean GCOS-24 score increased significantly from 106.79 (SD = 16.36) before counselling to 125.11 (SD = 15.42) after counselling (p < 0.001). Only 27.3% of parents were aware of genetic disorders, reflecting their limited baseline knowledge. A one-way ANOVA analysis showed a statistically significant difference in GCOS-24 score improvements based on parental education level (F=4.035, p=0.008) with parents with primary school education showing the greatest improvement compared to those with high school (p < 0.05). Conclusions: Genetic counselling significantly enhanced parent empowerment, as evidenced by increased GCOS-24 scores. These findings emphasize the importance of expanding genetic counselling services and educational initiatives in Indonesia to improve awareness and support for families managing ID.